25-hydroxyvitamin D levels in children of different ages and with varying degrees of Helicobacter pylori infection and immunological features - Ma, Peng-fei; Dai, Qun; Chu, Jing; Zhuo, Lin; Chen, Yi; Cheng, Rong; Wu, Cheng; Yuan, Li-Ping (Frontiers in Pediatrics, 2023)
Abstract Background: Helicobacter pylori (HP) is a major cause of upper digestive tract diseases. However, the relationship between HP infection and 25-hydroxyvitamin D (25(OH)D) levels in children has not been fully elucidated. This study investigated the levels of 25(OH)D in children of different ages and with varying degrees of HP infection and immunological features as well as the correlations between 25(OH)D levels in children infected with HP and their ages and degrees of infection. Materials and Methods: Ninety-four children who underwent upper digestive endoscopy were divided into an HP-positive group without peptic ulcers (Group A), an HP-positive group with peptic ulcers (Group B) and an HP-negative control group (Group C). The serum levels of 25(OH)D and immunoglobulin and the percentages of lymphocyte subsets were determined. HP colonization, the degree of inflammation, and the degree of activity were further evaluated by HE staining and immunohistochemical staining in gastric mucosal biopsy. Results: The 25(OH)D level of the HP-positive groups (50.93±16.51 nmol/L) was significantly lower than that of the HP-negative group (62.89±19.18 nmol/L). The 25(OH)D level of Group B (47.79±14.79 nmol/L) was lower than that of Group A (51.53±17.05 nmol/L) and was significantly lower than that of Group C (62.89±19.18 nmol/L). The 25(OH)D level decreased with increasing age, and there was a significant difference between Group C subjects who were ≤5 years old and those who were aged 6-9 years and ≥10 years. The 25(OH)D level was negatively correlated with HP colonization (r= -0.411, P<0.01) and the degree of inflammation (r= -0.456, P<0.01). The percentages of lymphocyte subsets and immunoglobulin levels among Groups A, B and C were not significantly different. Conclusions: The 25(OH)D level was negatively correlated with HP colonization and the degree of inflammation. As the age of the children increased, the level of 25(OH)D decreased, and the susceptibility to HP infection increased.